Proper Pricing - Kapoor, Supriya (The Telegraph, 2024)
If you’ve ever been stung with an expensive flight at Christmas or an overpriced hotel in August, you’ll know full well how costs can fluctuate throughout the year when it comes to travel spending. However, following the furore about Oasis tickets leaping from face values of between £65 and £250 to more than £400, it’s becoming clear how raising prices based on demand — the dynamic pricing model — is used in different industries
PUBLISHED